Study of electromagnetic vibration energy harvesting with free/impact motion for low frequency operation. (4th August 2015) - Haroun, Ahmed; Yamada, Ichiro; Warisawa, Shin׳ichi
Abstract: This paper presents study of an electromagnetic vibration energy harvesting configuration that can work effectively at low frequencies. Unlike the conventional form of vibration energy harvesters in which the mass is directly connected to a vibrating frame with spring suspension, in the proposed configuration a permanent magnet mass is allowed to move freely within a certain distance inside a frame-carrying coil and make impacts with spring end stops. The free motion distance allows matching lower vibration frequencies with an increase in the relative amplitude at resonance. Hence, significant power could be generated at low frequencies. A nonlinear mathematical model including impact and electromagnetic induction is derived. Study of the dynamic behaviour and investigation of the system performance is carried out with the aid of case study simulation. The proposed harvester shows a unique dynamic behaviour in which different ways of response of the internal relative oscillation appear over the range of input frequencies. A mathematical condition for the response type at which the higher relative amplitude appears is derived, followed by an investigation of the system resonant frequency and relative amplitude. The resonant frequency shows a dependency on the free motion distance as well as the utilized mass and spring stiffness. Simulation and experimental comparisons are carried out between the proposed harvester and similar conventional one tuned at the same input frequency. The power generated by the proposed harvesting configuration can reach more than 12 times at 11 Hz in the simulation case and about 10 times at 10 Hz in the experimental case. Simulation comparison also shows that this power magnification increases by matching lower frequencies which emphasize the advantages of the proposed configuration for low frequency operation. Highlights: We present an electromagnetic vibration energy harvester based on free/impact motion. The proposed harvester has a resonant behaviour. However, it shows a unique way of oscillation. Its resonant frequency can be shifted to lower range with an increase in the resonant relative amplitude Simulation and experimental comparison between the proposed harvester and similar conventional one shows its advantages at low frequencies.